West Nile Virus Infection in Plasma of Blood and Plasma Donors, United States - Planitzer, Christina B. (Centers for Disease Control and Prevention, 2009)
This study investigated the association of ongoing West Nile virus (WNV) infections with neutralizing antibody titers in US plasma-derived intravenous immune globulin released during 2003–2008. Titers correlated closely with the prevalence of past WNV infection in blood donors, with 2008 lots indicating a prevalence of 1%.